Measurement of Parathyroid Hormone Level after Total Thyroidectomy in Prediction of Hypocalcaemia - Saha, Gobinda Chandra; Rahman, Mohammad Ziaur; Rashid, Md Shoeb Ur; Chhanda, Chhamita Sultana; Dey, Debashis (Sir Salimullah Medical College Journal, 2022)
Background: Parathyroid dysfunction leading to symptomatic hypocalcemia is not uncommon following a total or completion thyroidectomy and is often associated with significant patient morbidity and a prolonged hospital stay. Objectives: To investigate whether postoperative parathyroid hormone level is a parameter to identify hypocalcaemia after total thyroidectomy. Methods: This prospective longitudinal study was carried out with variety of thyroid disorders with indication of total thyroidectomy at BSMMU. Total 103 patient were selected following the inclusion and exclusion criteria. The routine clinical assessment and the preoperative laboratory investigations of the study population were performed before operation. Preoperative and postoperative levels of serum PTH and serum calcium level were measured. Results: Immediate post-operative period 17(16.50%) patients PTH level were low (<14 pg/ ml). The mean PTH in immediate post-operative was 36.79±21.71 pg/ml. Regarding the distribution of the study patients by serum calcium, it was observed that 20.39% patients belonged to low (<8 mg/dl) serum calcium. The mean serum calcium level was 8.47±1.19 (mg/dl) with ranged from 2.1 to 10.6 (mg/dl). Among the study population 11 patient developed symptomatic hypocalcemia. Most 72.7% the patient, symptomatic hypocalcemia developed after 48 hours of operation. Conclusion: Hypocalcaemia after total or completion thyroidectomy is not uncommon in our population. If we measure a single parathyroid hormone level in postoperative period that can reflect early result and help to take necessary measure to avoid hypocalcaemic effect. Low intraoperative PTH levels during thyroid surgery are therefore a feasible predictor of postoperative hypocalcemia. Sir Salimullah Med Coll J 2022; 30: 103-107